Oficinas de arte: em meio a falas sintomáticas, encontros singulares com a velhice - Gomes, Ana Célia Soares (2018)
This dissertation proposes a reflection on the way Arts Workshops handle the social inclusion of the aphasic and demented elderly who are assisted by the Centro de Atendimento a Afásicos (CAAf) – Center of aphasic care – of the Divisão de Ensino e Reabilitação dos Distúrbios da Comunicação (Derdic) – Communication Disturbs Rehabilitation and Teaching Unit – within Pontifícia Universidade Católica de São Paulo (PUC-SP) – Catholic Pontifical University of São Paulo – which have been under my responsability since 2015. Nevertheless, this has caused some questioning on praxis and its effects on the social lives of double-marginalized people. Not only does the “disease isolates” (SIGERIST, 1932, p. 107 apud CANGUILHEM, 1995, p. 90) but contemporary societies tend to treat the elderly as “outcasts" (BEAUVOIR, 1990). Taking into account both the “double exclusion” and the potencial of inclusion of the arts, my main aim was to systematize the activities carried out in the Workshops thus making them easier to replicate. In order to achieve that I have outlined the following specific goals: (1) question the modus operandi of the relationships formed (among people; of a person and his/her artistic expression and/or creative potential; of all and each of their differences presented through their displays of speaking/hearing; of workers and patients and their disparities (i.e. normality x pathology); (2) identify the transformative impact, both subjective and social, of their participation in said Workshops; (3) explore a way that Workshops could provide and/or improve speech therapy treatment. Not only have I chosen the critic review of the theme’s bibliography (which involved an analysis of the ageing process, old age, pathologies and speech therapy and social inclusion/exclusion) but also a survey to help answer the questions surrounding it. In order to analyze all the gathered data I have chosen a “Case Study”. The results have allowed me to reach the conclusion that art is indeed a powerful tool to strengthen bonds. It also opens new paths for people who are in a double-vulnerability situation (old and sick) to claim and establish their place in the complex contemporary social dinamics